Detection and size measurements of pulmonary nodules in ultra-low-dose CT with iterative reconstruction compared to low dose CT. Issue 3 (March 2016) - Sui, Xin; Meinel, Felix G.; Song, Wei; Xu, Xiaoli; Wang, Zixing; Wang, Yuyan; Jin, Zhengyu; Chen, Jiuhong; Vliegenthart, Rozemarijn; Schoepf, U. Joseph
Highlights: Lung cancer is the leading cause of death from cancer. Lung cancer screening with LDCT can reduce death. The radiation dose of ultra-low-dose CT is similar to chest radiograph. The ultra-low-dose CT has high sensitivity for pulmonary nodule detection. Solid nodule measurement on ultra-low-dose CT is comparable to LDCT. Abstract: Background: In this study, the accuracy of ultra-low-dose computed tomography (CT) with iterative reconstruction (IR) for detection and measurement of pulmonary nodules was evaluated. Methods: Eighty-four individuals referred for lung cancer screening (mean age: 54.5 ± 10.8 years) underwent low-dose computed tomography (LDCT) and ultra-low-dose CT. CT examinations were performed with attenuation-based tube current modulation. Reference tube voltage and current were set to 120 kV/25 mÅs for LDCT and 80 kV/4 mÅs for ultra-low-dose CT. CT images were reconstructed with filtered back projection (FBP) for LDCT, and with FBP and IR for ultra-low-dose CT datasets. A reference standard was established by a consensus panel of 2 different radiologists on LDCT. Volume and diameter of the solid nodules were measured on LDCT with FBP and ultra-low dose CT with FBP and IR. Interobserver and interscan variability were analyzed and compared by the Bland–Altman method. Results: A total of 127 nodules were identified, including 105 solid nodules, 15 part solid nodules, 7 ground glass nodules. On ultra-low-dose CT scans, the effective radiation dose was 0.13 ± 0.11 mSv. A total of 113 (88.9%) and 110 (86.6%) true-positive nodules with FBP versus 117 (92.1%) and 118(92.9%) with IR were detected by two observers, respectively. The volume and size of the 105 solid nodules were measured, with mean volume/diameter of 46.5 ± 46.6 mm 3 /5.1 ± 1.6 mm. There was no significant difference in nodule volume or diameter measurements between ultra-low-dose CT and LDCT protocols for solid nodules. Conclusions: Ultra-low-dose CT with iterative reconstruction has high sensitivity for lung nodule detection without significant difference in nodule size and volume measurement compared to LDCT.